2014
DOI: 10.2147/opth.s41000
|View full text |Cite
|
Sign up to set email alerts
|

An emerging treatment option for glaucoma: Rho kinase inhibitors

Abstract: Rho kinase (ROCK) inhibitors are a novel potential class of glaucoma therapeutics with multiple compounds currently in Phase II and III US Food and Drug Administration trials in the United States. These selective agents work by relaxing the trabecular meshwork through inhibition of the actin cytoskeleton contractile tone of smooth muscle. This results in increased aqueous outflow directly through the trabecular meshwork, achieving lower intraocular pressures in a range similar to prostaglandins. There are also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 65 publications
4
45
0
Order By: Relevance
“…While inhibitors of GSK-3β have been identified as an important strategy for the treatment of CNS disorders including AD [49], to date, there are few studies investigating whether these molecules could be of benefit for the treatment of glaucoma. Elevated levels of RhoA are reported in the ONH of human eyes with glaucoma [66], and Rho kinase (ROCK) inhibitors are increasingly recognised as a promising therapeutic strategy for the treatment of glaucoma, indicating shared pathology [184]. In addition to the well-established IOP-modulating activity of these agents, ROCK inhibitors have been found to promote RGC axonal regeneration in both murine and feline models of optic nerve crush, a subject recently reviewed by Van de Velde et al [177].…”
Section: Mechanisms Of Rgc and Axonal Deathmentioning
confidence: 99%
“…While inhibitors of GSK-3β have been identified as an important strategy for the treatment of CNS disorders including AD [49], to date, there are few studies investigating whether these molecules could be of benefit for the treatment of glaucoma. Elevated levels of RhoA are reported in the ONH of human eyes with glaucoma [66], and Rho kinase (ROCK) inhibitors are increasingly recognised as a promising therapeutic strategy for the treatment of glaucoma, indicating shared pathology [184]. In addition to the well-established IOP-modulating activity of these agents, ROCK inhibitors have been found to promote RGC axonal regeneration in both murine and feline models of optic nerve crush, a subject recently reviewed by Van de Velde et al [177].…”
Section: Mechanisms Of Rgc and Axonal Deathmentioning
confidence: 99%
“…(Challa and Arnold, 2014; Nakajima et al, 2005; Rao et al, 2005; Rao et al, 2001; Wang and Chang, 2014) In addition, Rock inhibitors have been reported to increase ocular blood flow to the optic nerve head, enhancing RGC survival and axon regeneration after ischemic injury. (Sugiyama et al, 2011; Tokushige et al, 2011) Rock inhibitors also reduce scar formation and inflammation following glaucoma filtering surgery.…”
Section: Introductionmentioning
confidence: 99%
“…(Honjo et al, 2007) These data suggest that Rock inhibitors may have additional beneficial effects for the management of glaucoma other than reduction of IOP. (Challa and Arnold, 2014; Wang and Chang, 2014; Yamamoto et al, 2014)…”
Section: Introductionmentioning
confidence: 99%
“…The fibrogenic effect caused by TGFβ2 is believed to be mediated, in part, by activated RhoGTPase/Rho-associated kinase (ROCK). ROCK-inhibitors are a novel potential class of glaucoma therapeutics offering distinct applications including reduced IOP, improved ocular blood flow, inhibition of postoperative scarring, and even neuroprotection910. With demonstrated effectiveness in animal models, several ROCK-inhibitors are currently undergoing Phase II and III clinical trials in glaucoma1011.…”
mentioning
confidence: 99%
“…ROCK-inhibitors are a novel potential class of glaucoma therapeutics offering distinct applications including reduced IOP, improved ocular blood flow, inhibition of postoperative scarring, and even neuroprotection910. With demonstrated effectiveness in animal models, several ROCK-inhibitors are currently undergoing Phase II and III clinical trials in glaucoma1011. ROCK inhibitors can affect the contractile properties of HTM cells, α-smooth muscle actin (α-SMA) expression, ECM accumulation in the outflow pathway and aqueous humor outflow9101112.…”
mentioning
confidence: 99%